Development of Student Textbooks and Lecture Guides for Business and Office English Courses based on Audio - Trisnawati, Novi; Rahmawati, Fitriana; Wulandari, Siti Sri; Wibowo, Amiruddin Hadi; Raji-Ellams, Zaynab Bolanle (IKIP Widya Darma Surabaya, 2026)
Objectives: This study aimed to develop and assess the feasibility of an audio-based Student Textbook and Lecture Guide for the Business and Office English course in the Office Administration Education Study Program, Faculty of Economics and Business Universitas negeri Surabaya that address the lack of updated course-aligned teaching materials. Method: This study used Research and Development approach with ADDIE instructional design model, but the process was limited to the implementation stage after wider-scale trials and revisions. The product was validated by a material expert and a media expert, followed by student try-outs using questionnaires (small group of 10 students and large group of 40 students from the 2023 cohort). Results: Needs analysis showed the program had no updated textbook aligned with the semester lesson plan; learning relied mainly on lecturer-made PowerPoints and conventional instruction considered less effective for achieving course outcomes. Expert validation indicated the material aspect was feasible with an average score 67 and the media aspect was highly feasible with average score 86. Student responses in the large-group trial showed an overall average score of 94 considered as highly feasible, supporting its use as a learning resource. Novelty: This study provides practical evidence that integrating audio-based exercises into a course-specific textbook and lecture guide based on semester lesson plan and Merdeka curriculum highly feasible model for supporting independent practice in Business and Office English for non-English department.